Design of A Web-Based Geographic Information to Show Spatial Information of Land Used for Horticulture - Kawung, Yosua; Tooy, Dedie; Pakasi, Sandra (Agro Bali : Agricultural Journal, 2023)
Information technology is necessary today, especially to present information on land planted with horticultural crops in an area. The need to obtain fast, precise, and accurate information with the existence of an internet network via smartphones has proven to be very helpful in presenting information to local governments and buyers of horticultural products in obtaining products that can be traded to the public. Often the difficulties that occur in several agricultural areas, the information available is only in the form of location data tables and the exact location is unknown. The problem is that this information is not yet available in some areas. Therefore this study aims to create a web-based information system by compiling, storing and showing information about existing horticultural plants by taking a case example in Girian District, Bitung City, North Sulawesi Province. Web-based information is created by combining the information using a geographic information system (GIS) that displays descriptive text, tables, and images based on spatial location. The results of this study are expected to be useful for farmers in Girian District and local governments in planning and evaluating horticultural farming more easily. The research was conducted by building a web using the Windows 10 pro operating system platform, ArcGIS 10.8 software, Google Earth, Microsoft Word, and XML as a web server, and WordPress 5.4.1 as a content management system. Websites that have been built are tested for performance with gtmatrix with good results. The website that has been built can provide information related to horticultural crops in Girian District, Bitung City, especially information about Girian District and also the location of horticultural crops in Girian District, Bitung City.